La cooperacion fiscal internacional y los paises en vias de desarrollo. - FitzGerald, V (2001)
The current process of globalisation based on the free circulation of capital represents an opportunity for developing countries to expand their production capabilities, but at the same time it hinders the effective taxation of income from assets held by non residents. This article tackles the problem of tax competition between countries, conflicts concerning taxable bases and double taxation treaties, and presents a simple model which illustrates the dilemma facing small, open economies which seek to promote private investment and fund their social infrastructure. This theoretical framework is contrasted with international fiscal practice in terms of statistical evidence and progress in information sharing and the control of tax havens. In conclusion the need is stressed to establish a system of fiscal cooperation on a world scale that can watch over the interests of developing economies.